Effect of Regulatory Compliance on the relationship between Public Procurement of Innovation and Supply Chain Performance - Ratemo, Bonface Matayo; Karanja, Dr. Ngugi (International Journal of Scientific Research and Management (IJSRM), 2017)
The Kenya government has n recent times aggressively advocated for the utilization of publicprocurement‘s buying power to stimulate and diffuse innovation, but the additional requirement placed onpublic procurement has made procurement practitioners cautious about the move given that publicprocurement is a regulated process whose ultimate agenda is to ensure value for money is achieved.Surprisingly, extant literature on Supply chain Performance in Kenya owned State Corporations has paidmuch attention to the direct relationship between functional aspects and supply chain performance, to theexclusion of the moderating effect of regulatory compliance on these relationships. This paper sought toexamine the effect of regulatory compliance on the relationship between public procurement of innovationand supply chain performance in Kenya owned State Corporations. The study employed a cross-sectionalcensus survey design targeting 187 Kenya owned State Corporations. Primary data was collected usingclose and open ended questionnaires while secondary data was retrieved from Public ProcurementRegulatory Authority website. The results revealed that regulatory compliance had a positive andstatistically significant effect on supply chain performance. The study recommends for regulatorycompliance as interventionist measure in the utilisation of public procurement of innovation to stimulatediffusion of innovation